A Socialist Analysis of the Mutual Aid Solidarity During the #EndSARS Protest in Multi-Religious Nigeria - Uroko, Favour C. (Kennedy Institute of Ethics journal, 2023)
This study describes the results of a social analysis of mutual aid solidarity during Nigeria's #EndSARSprotests against Special Anti-Robbery Squad (SARS) brutality in Nigeria. The results reveal that the protests achieved success with the assistance of mutual aid solidarity networks. Yet there is a dearth of literature exploring the reasons for this accomplishment. Nigeria is a country where everything done usually has a religious coloration and interpretation; however, the 2020 mutual aid solidarity in the #EndSARS protests proved otherwise. Using in-depth interviews, data were elicited from 20 youths, including participants and observers during the #EndSARS mutual aid solidarity protests. Using a phenomenological approach, this study found that the mutual aid support group transcended traditional geopolitical, gender, and religious barriers, and youth and the elderly participated in the protest. Further results show that the 2020 #End-SARS mutual aid solidarity brought about an accountable and transparent civil society, including the financial disbanding of the Nigerian Police Force, the SARS unit responsible for extrajudicial killings. The findings also indicate that Nigerian politicians are the real problem, not religion. Recommendations are discussed.